Strategi Pengembangan Usaha Pada UMKM Dimsum Bandung (Studi Kasus:Mami Dimsum Bandung) - Nuriana, Mellysha Septiani Putri Dwi; Wijaya, Fanji; Herlinawati, Erna (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research is a call to action, aiming to urgently formulate a business development strategy for Mami Dimsum Bandung MSMEs using SWOT analysis and Business Model Canvas (BMC). Given the crucial role of MSMEs in the Indonesian economy, especially in West Java, this research underlines the pressing need to develop appropriate strategies to improve competitiveness. The method used is descriptive qualitative, with primary data collection through interviews and secondary data from related literature. The results show that Mami Dimsum's main strengths lie in product quality and service, while its main weaknesses are limited capital and production capacity. Significant opportunities are found in the increasing demand for fast food products, while threats come from intense competition and regulatory changes. The proposed strategies include improving operational efficiency, strengthening customer relationships, and diversifying distribution channels. Implementing Business Model Canvas provides a thorough strategic overview of the key elements of the business, assisting Mami Dimsum in mapping out measurable and sustainable development steps